Chinese foods for longevity the art of long life - Lu, Henry C. (Pelanduk, 1990)
This practical guide explains the time-honoured Chinese tradition of eating for health and longevity, and shows how familiar food from your supermarket can help you build up your immune system -- the key to long life.